2007
DOI: 10.1111/j.1423-0410.2007.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐associated microchimerism

Abstract: Blood transfusion is a newly recognized cause of microchimerism, the stable persistence of a minor population of allogeneic cells. Relatively recent advances in polymerase chain reaction technology have spawned new information about the frequency and aetiology of transfusion-associated microchimerism (TA-MC). Although conceptually related to fetal-maternal microchimerism, TA-MC is a distinct and separate entity. Evidence of TA-MC has been strongest among patients with severe traumatic injuries who receive rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 53 publications
1
48
1
1
Order By: Relevance
“…In the Rivers study, red cell transfusions were initiated if the mixed venous oxygen tension was less than 70% after respiratory, fluid and vasopressor support and if the hematocrit was less than 30%. This seems to contradict other studies that showed no difference in mortality when red cells were given to critically ill patients [47] or, in fact, made them worse [48,49] because of infection and lung injury. As red cell transfusion was part of a 'bundle' of interventions, it is hard to discern what role individual parts had in the reduction of mortality.…”
Section: The Early Treatment Of Sepsis and Goals Of Resuscitationcontrasting
confidence: 76%
“…In the Rivers study, red cell transfusions were initiated if the mixed venous oxygen tension was less than 70% after respiratory, fluid and vasopressor support and if the hematocrit was less than 30%. This seems to contradict other studies that showed no difference in mortality when red cells were given to critically ill patients [47] or, in fact, made them worse [48,49] because of infection and lung injury. As red cell transfusion was part of a 'bundle' of interventions, it is hard to discern what role individual parts had in the reduction of mortality.…”
Section: The Early Treatment Of Sepsis and Goals Of Resuscitationcontrasting
confidence: 76%
“…Furthermore, we observed both decreased survival and more aggressive tumor behavior for male mice, as compared to female mice, inoculated with pancreatic cancer cells following transfusion of female blood [23, 24]. Such differences may involve alloimmunization [22, 25] or even microchimerism [26] of multiparous female donors.…”
Section: Introductionmentioning
confidence: 99%
“…HLA sharing promotes lymphocyte engraftment in transfusion associated GVHD and microchimerism [32,33], nonetheless, it may not be necessary to facilitate PLS in RT patients. Kidney donor-recipient pairs were HLA mismatched and PLS occurred in 2 patients despite the presence of HLA disparity between donors and recipients.…”
Section: Discussionmentioning
confidence: 98%